Niumamenos: feminism, pedagogies and resistance poetics - Adriana Alves da Silva (Universidade Federal de Santa Catarina, 2018)
The present work presents reflections woven in a research and creation course in the field of childhood pedagogy, starting from the symbolic dimensions of the fight against femicide in the context of day care. Part of the research was carried out in a PhD in Italy in 2012 and the current teaching experience in a nursery school of the municipal network of Florianopolis. This complex of experiences includes educational actions carried out in various contexts and agencies of the Infant Education, including infants, young children, teachers, families and researchers. Through artistic interventions in a project en titled "Fairy Tales in Motion: Feminism, Education and Art, we seek to promote creative processes with female characters from Western classical literature: Cinderella, Little Red Riding Hood, the poor orphan of the Red Shoe, among others having as a methodological strategy The use of the "fairy tales / horror" literature as a key to the problematization of violence that pervades gender relations and which has been narrated for centuries and generations throughout the world.The proposal seeks to deconstruct stereotypes and norms of behavior between men / boys and women / girls and aims to provoke displacements of meanings, transformations and creations of new narratives, with possibilities in the lines of the stories of sowing feminist concepts: from sorority, feminine empowerment, emerging political principles to a decolonizing emancipatory pedagogy.